The Periodic Table and The Learning of Chemistry: Possibilities of Integrating Robotics and Concept-Based Approaches in Teaching - Mhlongo, Thabo; Sedumedi, Thomas Dipogiso (Yayasan Azka Hafidz Maulana, 2024)
In this study, the authors investigate the potential of integrating robotics technology and concept-based teaching approaches to enhance the learning of abstract Chemistry concepts, focusing on the periodic table as both subject matter and tool. Utilizing a quasi-experimental design, the research employs descriptive quantitative and qualitative methods for data collection, including pre- and post-test experimental designs. Results suggest that combining robotics with concept-based teaching improves learners' deep understanding of chemistry concepts. The study highlights the promising benefits of integrating robotics technology and a concept-based approach for teaching chemistry, emphasizing the need for further research in this area.